Prediction of maximum strain and strain rate in SHPB specimens based on energy analysis - Nurizzatul Atikha, Rahmat (2013)
The split Hopkinson pressure bar (SHPB) technique developed by H. Kolsky has been widely used to determine stress-strain curves of materials at strain rates from 102 to 104 s'. In the SHPB method, it is usually impossible to predict the maximum strain and strain rate obtainable in the specimen before testing even if an impact velocity of a striker bar, diameters and acoustic impedances (pc) of the Hopkinson bars and the specimen geometry are specified. This is because the strain rate dependence of test materials is unknown' until the SHPB tests are conducted. The objective of the present work is to predict the maximum plastic strain and strain rate in the SHPB specimen based on the energy analysis using rate-independent plasticity. Two different material models are used to express the rate-independent mechanical behavior of the test materials. The present energy analysis enables one to approximately estimate the maximum plastic strain and strain rate in the SHPB specimen in advance from the static properties of the test materials. The prediction accuracy of the energy analysis is checked by comparison with the experimental results for three high-strength aluminum alloys obtained from the SHPB tests. It is demonstrated that the maximum strain and strain rate in the SHPB specimens are slightly overestimated by the energy analysis due to the neglect of the kinetic energy within them.